Circulating human papillomavirus DNA detected using droplet digital PCR in the serum of patients diagnosed with early stage human papillomavirus‐associated invasive carcinoma. (28th June 2016) - Jeannot, Emmanuelle; Becette, Véronique; Campitelli, Maura; Calméjane, Marie‐Ange; Lappartient, Emmanuelle; Ruff, Evelyne; Saada, Stéphanie; Holmes, Allyson; Bellet, Dominique; Sastre‐Garau, Xavier
Abstract: Specific human papillomavirus genotypes are associated with most ano‐genital carcinomas and a large subset of oro‐pharyngeal carcinomas. Human papillomavirus DNA is thus a tumour marker that can be detected in the blood of patients for clinical monitoring. However, data concerning circulating human papillomavirus DNA in cervical cancer patients has provided little clinical value, due to insufficient sensitivity of the assays used for the detection of small sized tumours. Here we took advantage of the sensitive droplet digital PCR method to identify circulating human papillomavirus DNA in patients with human papillomavirus‐associated carcinomas. A series of 70 serum specimens, taken at the time of diagnosis, between 2002 and 2013, were retrospectively analyzed in patients with human papillomavirus‐16 or human papillomavirus‐18‐associated carcinomas, composed of 47 cases from the uterine cervix, 15 from the anal canal and 8 from the oro‐pharynx. As negative controls, 18 serum samples from women with human papillomavirus‐16‐associated high‐grade cervical intraepithelial neoplasia were also analyzed. Serum samples were stored at −80°C (27 cases) or at −20°C (43 cases). DNA was isolated from 200 µl of serum or plasma and droplet digital PCR was performed using human papillomavirus‐16 E7 and human papillomavirus‐18 E7 specific primers. Circulating human papillomavirus DNA was detected in 61/70 (87%) serum samples from patients with carcinoma and in no serum from patients with cervical intraepithelial neoplasia. The positivity rate increased to 93% when using only serum stored at −80°C. Importantly, the two patients with microinvasive carcinomas in this series were positive. Quantitative evaluation showed that circulating viral DNA levels in cervical cancer patients were related to the clinical stage and tumour size, ranging from 55 ± 85 copies/ml (stage I) to 1774 ± 3676 copies/ml (stage IV). Circulating human papillomavirus DNA is present in patients with human papillomavirus‐associated invasive cancers even at sub‐clinical stages and its level is related to tumour dynamics. Droplet digital PCR is a promising method for circulating human papillomavirus DNA detection and quantification. No positivity was found in patients with human papillomavirus‐associated high grade cervical intraepithelial neoplasia.